REPRESENTASI NILAI KESEMPURNAAN, KESATUAN DAN KEBERANIAN PADA LOGO BARU PT. DARTA MEDIA INDONESIA (KASKUS.CO.ID) (Studi Analisis Semiotik Charles Sanders Peirce Mengenai Logo Baru Pt. Darta Media Indonesia (Kaskus.Co.Id) Sebagai Corporate Identity Perusah - Wildan Maulana Firdaus; Kokom Komariah; Centurion Chandratama Priyatna (SEMIOTIKA: Jurnal Komunikasi, 2017)
This research employed qualitative method with semiotics analysis approach from Charles Sanders Peirce and data is collected by means of media text analysis, documentation and literature studies..Result shows that the symbol in the logo of KASKUS.CO.ID brand is divided into picture, letter marks, color and composition, in which each category presented its own meaning. New KASKUS.CO.ID logo as a corporate identity is the representation of company’s value, namely Unity, perfection and courage. Those values implied in KASKUS’ new logo has a philosophy in representing: Perfection where KASKUS want to enhance the site; Unity where KASKUS was built by a community; and Courage where KASKUS is a forum for the community to express their ideas.It is recommended that in underlining company's vision, the logo should have an additional typographic form of corporate tagline "The Largest Indonesian Forum” attached.Keywords : Semiotics, Charles Sanders Peirce, Logo, KASKUS